COMFORT-IPE: Communication Training for Interprofessional Patient-Centered Care - Elaine M. Wittenberg-Lyles; Joy V. Goldsmith; Betty Ferrell; Debra Parker Oliver; Andrea Lynn Pfeifle (Association of American Medical Colleges, 2012)
Abstract Introduction This resource presents a series of communication skills training modules designed to highlight interprofessional care and communication. Each module of the COMFORT (Communication, Orientation/Opportunity, Mindfulness, Family, Openings, Relating, Team) curriculum can stand alone as a teaching activity or can be integrated into a new or existing course. Methods Modules C (narrative clinical communication) and F (family caregivers) provide beginner-level instruction, while modules M (mindfulness), O/O (orientation), and T (team) provide intermediate instruction. Finally, modules O (openings) and R (relating) provide advanced communication skills and are intended for learners who have clinical observation experience. Results Our preliminary research on the effectiveness of the COMFORT communication curriculum has included both clinical audiences and student learners. More than 75% of clinicians exposed to COMFORT report that the activity is considered useful to clinical practice and modules are easy to understand and relevant. Students' course evaluation score was average of 4.77 out of 5.0, indicating that students perceived the COMFORT communication training as providing knowledge they did not previously possess prior to the course. Discussion The order of the modules is arbitrary; instructors may determine the order of modules, which modules to cover (not all modules need to be taught and should complement larger course content/goals), and which module is appropriate based on learning level and intended audience.